Analisis Sosiologi Sastra Pada Lagu - Sahri Nova Yoga; Farida Isroani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Songs are a form of literary work. This is in accordance with the opinion of Sugono (2008:77) who states that,